Differential effects of single-stranded DNA binding proteins (SSBs) on uracil DNA glycosylases (UDGs) from Escherichia coli and mycobacteria. - Purnapatre, K (1999)
Deamination of cytosines results in accumulation of uracil residues in DNA, which unless repaired lead to GC-->AT transition mutations. Uracil DNA glyco-sylase excises uracil residues from DNA and initiates the base excision repair pathway to safeguard the genomic integrity. In this study, we have investigated the effect of single-stranded DNA binding proteins (SSBs) from Escherichia coli (Eco SSB) and Mycobacterium tuberculosis (Mtu SSB) on uracil excision from synthetic substrates by uracil DNA glycosylases (UDGs) from E. coli, Mycobacterium smegmatis and M.tuberculosis (referred to as Eco -, Msm - and Mtu UDGs respectively). Presence of SSBs with all the three UDGs resulted in decreased efficiency of uracil excision from a single-stranded 'unstructured' oligonucleo-tide, SS-U9. On the other hand, addition of Eco SSB to Eco UDG, or Mtu SSB to Mtu UDG reactions resulted in increased efficiency of uracil excision from a hairpin oligonucleotide containing dU at the second position in a tetraloop (Loop-U2). Interestingly, the efficiency of uracil excision by Msm UDG from the same substrate was decreased in the presence of either Eco- or Mtu SSBs. Furthermore, Mtu SSB also decreased uracil excision from Loop-U2 by Eco UDG. Our studies using surface plasmon resonance technique demonstrated interactions between the homologous combinations of SSBs and UDGs. Heterologous combinations either did not show detectable interaction (Eco SSB with Mtu UDG) or showed a relatively weaker interaction (Mtu SSB with Eco UDG). Taken together, our studies suggest differential interactions between the two groups (SSBs and UDGs) of the highly conserved proteins. Such studies may provide important clues to design selective inhibitors against this important class of DNA repair enzymes.